The impact of diurnal variations on emergence delirium following general anesthesia and surgery in children - Wei, Wei; Xie, Haihang; Xu, Yingyi; Qin, Jingwen; Guo, Xinying; Song, Xingrong; Yu, Gaofeng; Zhang, Na; Ma, Daqing; Tan, Yonghong; Zhao, Tianyun (Frontiers in Pediatrics, 2024)
Background: Emergence delirium (ED) is a widely recognised issue that prolongs mechanical ventilation and Post-Anesthesia Care Unit (PACU) resuscitation time, consequently increasing hospital costs and mortality. Postoperative disturbance in circadian rhythms, commonly leading to sleep disorders, have been identified as a significant risk factor for ED. However, the influence of surgery timing (morning vs. afternoon) on the incidence of ED in pediatric patients undergoing general anesthesia remains unknown. Methods: Patients aged 2-6 years operated under general anaesthesia with a Bispectral Index (BIS) value between 50-60 were categorized based on anesthesia start time into Morning Surgery Group (Group M, 8:00 -12:00) and Afternoon Surgery Group (Group A, 13:00 -17:00). The primary outcome was the incidence of ED assessed by the Cornell Assessment of Pediatric Delirium (CAPD) score post-extubation. Secondary outcomes included extubation time, duration of PACU stay, postoperative adverse events and complications. Results: We recruited 560 children who were randomly assigned to the Group M and the Group A (280/group).Compared to Group M, Group A exhibited a significantly higher incidence of ED (p < 0.001), elevated CAPD scores (p < 0.001), and prolonged PACU stays (p < 0.001). Notably, there was no significant difference in extubation time and anaesthesia-related adverse events or other postoperative complications between the groups. Conclusion: Our study highlights the surgery timing significantly effects the incidence of ED, CAPD scores and PACU stay duration in children. Further validation of these findings may guide future strategies to reduce ED.